Screening of cognitive deficits in bedridden eldery: experience report - Ana Paula Moura Pontes Nunes, Joaquim José Marques da Silva, Samuel Moura Carvalho, Adriana de Azevedo Paiva, Márcio Dênis Medeiros Mascarenhas, Viriato Campelo (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.8esp85-88